PENGARUH KINERJA GURU TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS XI DI SMA NEGERI 3 SIAK HULU - Faransiska, Debi; Kartikowati, Sri; Sumarno, Sumarno (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of teacher performance on student learning outcomes in Class XI Economic Subjects at Siak Hulu 3 High School. The population in this study was all class XI in State High School 03 Siak Hulu consisted of two classes with a total of 82 students, and using a sensus sampling technique. Data was collected by using questionnaires, and data was analyzed by descriptive technique. Analysis of the data used is descriptive analysis. Result of the study showed that the performance of Economic Teachers in SMA Negeri 03 Siak Hulu in general is in the category of being in a fairly good category. While the learning outcomes of students of economic subjects in class XI IPS 1 and XI IPS 2 at SMAN 03 Siak Hulu are in the poor category. Teacher performance has a significant positive effect on student learning outcomes on economic subjects in class XI IPS SMAN 03 Siak Hulu.Key Words: Teacher Performance, Student Learning Outcomes